Representing Targets of Measurement Within Evidence-Centered Design - Ewing, Maureen; Packman, Sheryl; Hamen, Cynthia; Thurber, Allison Clark (Applied measurement in education, 2010)
In the last few years, the Advanced Placement (AP) Program® has used evidence-centered assessment design (ECD) to articulate the knowledge, skills, and abilities to be taught in the course and measured on the summative exam for four science courses, three history courses, and six world language courses; its application to calculus and English language arts subjects is in progress. The purpose of this article is to describe the methodology that was used with subject-matter experts (SMEs) to articulate the content and skills important in the domain, and then the iterative processes that were used to articulate the claims and evidence to represent the targets of instruction for AP courses, and by extension, the targets of measurement for the AP exams. Discussion will focus on how the use of ECD provides a strong foundation for ensuring the alignment among curriculum, instruction, and assessment while at the same time enhances the validity argument for test score interpretation.